Prevalence and Risk Factors of Trichuris trichiura Infection among Elementary School Students in Palipi District, Samosir Regency, North Sumatera, Indonesia - Elly Susanti Br. Sembiring; Lambok Siahaan; Inke Nadia Diniyanti Lubis; Yoan Carolina; Indri Adriztina (Jurnal Epidemiologi Kesehatan Komunitas, 2026)
Background: Infection with Trichuris trichiura continues to affect populations in tropical and subtropical regions, particularly school-aged children living in environments with inadequate sanitation. This study was conducted to estimate the prevalence of T. trichiura infection and to identify associated risk factors among elementary school students in Palipi District, Samosir Regency, North Sumatra, Indonesia.Methods: This cross-sectional study was conducted from January to March 2025 in five elementary schools in Palipi District, Samosir Regency. A total of 109 students who met the inclusion and exclusion criteria and agreed to participate were recruited through school-based screening. Stool samples were examined using the Kato–Katz method at the Parasitology Laboratory, Universitas Sumatera Utara. Data on handwashing habits, diarrhea history, stunting status, and nail hygiene were collected using structured assessments. Anthropometric measurements and hematological parameters were also recorded. The data analysis involved descriptive statistical methods and chi-square testing, with statistical significance set at p < 0.05.Result: The prevalence of trichuris trichiura infection was 14.7%. Diarrhea was significantly associated with infection (p = 0.010), while stunting, handwashing with soap, and nail hygiene were not significantly associated (p > 0.05). Infected children showed slightly lower mean height, BMI, and hemoglobin levels; however, these differences were not statistically significant..Conclusion : Trichuris trichiura infection remains a public health concern among elementary school students in Palipi District. Diarrhea was significantly associated with infection. Strengthening hygiene promotion and sanitation programs at the school and community levels may help reduce transmission.